Expression of the human interferon-gamma cDNA in yeast. - Derynck, R (1983)
Several plasmids which direct the expression of human interferon-gamma (IFN-gamma) cDNA in the yeast Saccharomyces cerevisiae under the transcriptional control of the 3-phosphoglycerate kinase (PGK) promoter have been constructed. Up to 25 x 10(6) units per liter culture of biologically active IFN-gamma are synthesized in yeast transformed with these expression plasmids. The amount of IFN-gamma mRNA in yeast transformed with the IFN-gamma expression plasmids is much lower than the amount of PGK mRNA present when the PGK gene and promoter are inserted on a similar plasmid. The major and three minor sites of transcription initiation have been localized. The major starting point of the IFN-gamma mRNA is at 4 basepairs upstream of the PGK mRNA start. All transcription starts map at an ApG as does PGK mRNA. The yeast IFN-gamma mRNA terminates in a specific segment of the 3' untranslated region of the IFN-gamma cDNA. The polyadenylation site at about 182-184 nucleotides 3' of the IFN-gamma stop codon is preceded by a sequence which is very similar to a sequence proposed to be involved in transcription termination and polyadenylation (49).